2020
DOI: 10.9734/jamcs/2020/v35i130242
|View full text |Cite
|
Sign up to set email alerts
|

Cubic Transmuted Gompertz Distribution: As a Life Time Distribution

Abstract: In this work, we proposed and studied the Cubic Transmuted Gompertz (CTG) distribution using the Cubic Transmuted family of distributions which was introduced by Rahman et al. [8] and based on cubic transmutation map. We studied the statistical properties of the new distribution which includes: rth moment, moment generating function order statistics, mean, variance, Renyl entropy. The CTG distribution was fitted to a real data set to demonstrate its flexibility and tractability in modelling real life data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…e cubic transmuted Lindley is a special case from the ranked transmuted Lindley introduced by [23], by making some reparameterization; however, we used the cubic transmuted family proposed by Rahman et al [38] to get the equations of the cubic transmuted Livley, which is a special case of the distribution proposed in [23]. Distribution is a special case from equation (4) that caused other new distributions to be introduced by Ansari et al [39]; Ogunde et al [40]; Wang and Bao [41]; Rahman et al [38]; Akter et al [42]; and so on, in order to introduce the proposed distribution, by substituting equation ( 2) into (4), which has the following distribution function:…”
Section: Cubic Transmuted Lindley Distributionmentioning
confidence: 99%
“…e cubic transmuted Lindley is a special case from the ranked transmuted Lindley introduced by [23], by making some reparameterization; however, we used the cubic transmuted family proposed by Rahman et al [38] to get the equations of the cubic transmuted Livley, which is a special case of the distribution proposed in [23]. Distribution is a special case from equation (4) that caused other new distributions to be introduced by Ansari et al [39]; Ogunde et al [40]; Wang and Bao [41]; Rahman et al [38]; Akter et al [42]; and so on, in order to introduce the proposed distribution, by substituting equation ( 2) into (4), which has the following distribution function:…”
Section: Cubic Transmuted Lindley Distributionmentioning
confidence: 99%
“…Granzotto et al [9] have suggested cubic rank transmuted Weibull, cubic rank transmuted loglogistic distributions etc. Bugra Saracoglu et al [18], studied the properties of cubic rank transmuted kumaraswamy distribution, Cubic transmuted Gompertz distribution was studied by Ogunde AA et al [19] etc.…”
Section: Cubic Rank Transmuted Kumaraswamy (Crtiw) Distributionmentioning
confidence: 99%
“…In this paper, we introduce a new generalization of G distribution which results in the application of the G distribution to the Nadarajah and Haghighi (NH) family of distribution proposed by [4] as an alternative to Gamma and Weibull distributions. Several variants of Gompertz distribution have been studied but not limited to the work of [5] who investigated the properties of Cubic Transmuted Gompertz Distribution, [6] studied the properties of Transmuted Gompertz Distribution, [7] developed and studied the properties of Beta Gompertz Makeham distribution. The properties of kumaraswamy Gompertz Makeham distribution were studied by [8], [9] investigated the structure and properties of Beta Gompertz distribution, [10] developed studied the McDonald Gompertz distribution, the exponentiated generalised extended Gompertz distribution was studied by [11].…”
Section: Introductionmentioning
confidence: 99%